1989
DOI: 10.1200/jco.1989.7.10.1447
|View full text |Cite
|
Sign up to set email alerts
|

Surgical adjuvant therapy of large-bowel carcinoma: an evaluation of levamisole and the combination of levamisole and fluorouracil. The North Central Cancer Treatment Group and the Mayo Clinic.

Abstract: A total of 401 eligible patients with resected stages B and C colorectal carcinoma were randomly assigned to no-further therapy or to adjuvant treatment with either levamisole alone, 150 mg/d for 3 days every 2 weeks for 1 year, or levamisole plus fluorouracil (5-FU), 450 mg/m2/d intravenously (IV) for 5 days and beginning at 28 days, 450 mg/m2 weekly for 1 year. Levamisole plus 5-FU, and to a lesser extent levamisole alone, reduced cancer recurrence in comparison with no adjuvant therapy. These differences, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
239
2
12

Year Published

1990
1990
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 653 publications
(259 citation statements)
references
References 22 publications
6
239
2
12
Order By: Relevance
“…There is some evidence that adjuvant chemo-or radiotherapy may improve local recurrence rates and survival (Laurie et al, 1989;Jones et al, 1989;Metzger, 1991). The ability to accurately detect patients who may need and respond favourably to additional treatment would be an advantage and would increase the likelihood of determining potential benefits of adjuvant therapy.…”
mentioning
confidence: 99%
“…There is some evidence that adjuvant chemo-or radiotherapy may improve local recurrence rates and survival (Laurie et al, 1989;Jones et al, 1989;Metzger, 1991). The ability to accurately detect patients who may need and respond favourably to additional treatment would be an advantage and would increase the likelihood of determining potential benefits of adjuvant therapy.…”
mentioning
confidence: 99%
“…1 Although surgical resection alone is potentially curative, local or distant recurrences develop in many patients, and those with the highest risk of recurrence are advised to receive fluorouracil-based systemic adjuvant chemotherapy, which has been shown to be beneficial in a number of cooperativegroup trials and analyses. [2][3][4][5][6][7][8][9][10][11][12] Traditional pathological staging systems have been useful in predicting the outcome of colorectal cancer, but it is now evident that these cancers are heterogeneous. The natural history of colorectal cancer correlates strongly with genetic alterations that occur during the progression from adenoma to carcinoma to metastatic disease.…”
mentioning
confidence: 99%
“…In addition to surgical excision of the primary tumor, many patients benefit from adjuvant chemotherapy or radiation therapy. [2][3][4][5][6][7][8][9][10][11] Previous studies have shown great variability in the care and outcome of patients with colorectal cancer. 12,13 Age-adjusted colon cancer mortality rates are significantly higher for Black patients than for White patients.…”
mentioning
confidence: 99%